Spindle Cell Hemangioendothelioma of the Temporal Muscle Resected with Zygomatic Osteotomy: A Case Report of an Unusual Intramuscular Lesion Mimicking Sarcoma - Tomohiro Minagawa; Takeshi Yamao; Ryuta Shioya (Case Reports in Surgery)
Spindle cell hemangioendothelioma (SCH) was originally described by Weiss and Enzinger (1986) as a low-grade angiosarcoma resembling both cavernous hemangioma and Kaposi's sarcoma. Recent studies suggest that SCH is a benign neoplasm or reactive lesion accompanying a congenital or acquired vascular malformation. Most SCHs present as one or more nodules affecting the dermis or subcutis of the distal extremities. Few reports describe SCH of the head and neck region; even fewer note intramuscular SCH. Here, we describe a case of SCH involving the temporal muscle mimicking soft tissue sarcoma, who had a successful surgical treatment with a coronal approach and zygomatic osteotomy.